2018
DOI: 10.1021/acs.jpca.7b12402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Basicity on the Hydrolysis of the Bi(III) Aqua Ion in Solution: An Ab Initio Molecular Dynamics Study

Abstract: Hydrolysis of the Bi(III) aqua ion under a range of solution conditions has been studied by means of ab initio molecular dynamics simulations. While the Bi(III) aqua ion is stable in pure water, there is an increasing degree of hydrolysis with the number of hydroxide anions in the medium. This is accompanied by a monotonic decrease of the total coordination number to an asymptotic value of ∼6, reached under extreme basicity conditions. Comparison of the simulated Bi(III) hydrolyzed species with the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
(120 reference statements)
1
13
0
Order By: Relevance
“…S6 †). 25,26 Moreover, the acid concentration imparts pore regulations to the mesoporous shells. A relatively low growth speed at a higher acid concentration benets the formation of ordered mesoporous shells, thus resulting in well-organized nanocages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6 †). 25,26 Moreover, the acid concentration imparts pore regulations to the mesoporous shells. A relatively low growth speed at a higher acid concentration benets the formation of ordered mesoporous shells, thus resulting in well-organized nanocages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the interactions between the functional groups of LM and bismuth iodide were observed by XPS, we preformed theoretical calculations for further investigations. According to the simulations, bismuth­(III) exists mainly as BiI 2+ and Bi­(OH) 2 + species (Figure S9) and often form hexadentate BiI­(H 2 O) 5 2+ and Bi­(OH) 2 (H 2 O) 4 + hydrated ions (Figure S10) in the experimental pH range . The same simulations were carried out for iodine, and the results showed that besides the aforementioned BiI 2+ , the only existed form of iodine was I – .…”
Section: Resultsmentioning
confidence: 84%
“…According to the simulations, bismuth(III) exists mainly as BiI 2+ and Bi(OH) 2 + species (Figure S9) and often form hexadentate BiI(H 2 O) 5 2+ and Bi(OH) 2 (H 2 O) 4 + hydrated ions (Figure S10) in the experimental pH range. 25 The same simulations were carried out for iodine, and the results showed that besides the aforementioned BiI 2+ , the only existed form of iodine was I − . Since collagen triple helices, the fundamental molecular building blocks of LM, were comprised of 18 amino acids, 26 we classified these amino acids into three categories negatively charged amino acids, positively charged amino acids along with uncharged amino acids, and picked out one or two typical amino acids in each category to perform the theoretical calculations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Under neutral pH, Ga(OH) 4 – is formed 16 and transferred into the anode side isolator solution or trapped by AEM. On the other hand, Bi(OH) 4 – is formed at pH higher than 10.5, 15 and the removal of Bi 3+ shifted the equilibrium of Bi species and quantitative transfer was achieved at relatively low concentrations. The details of the calibration curves, equations, and correlation coefficients are also summarized in Table S3 .…”
Section: Results and Discussionmentioning
confidence: 99%